The nature Of the Crimes Committed by The Iraqi Army Against Individuals According to National and International Law on October 16, 2017 - Wirya khamo Darwish; Sharee Khalid Marouf (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
In order to clarify and determine the nature of the crimes committed by the Iraqi army against individuals as a problem and the importance of this study in accordance with national and international laws on October 16, 2017. We worked to identify the elements that determine that nature in terms of the presence of the criminalization text and the pillars of those crimes and who has the right to file a criminal complaint in them and then determine the applicable law and the competent judiciary. Between the Iraqi penal code and the international criminal justice. Through the study of Iraqi penal laws - Penal Code No. 111 of 1969, Military Penal Code No. 13 of 1940, the International Criminal Court system, the Geneva Conventions of 1949, and their protocols. In documenting those crimes and working to investigate them, whether by the Iraqi national judiciary or the international court at the International Criminal Court. Because the crimes committed cannot be tolerated or ignored, they must be internationalized if they are not addressed by Parliament and the Iraqi authorities to begin investigating and prosecuting the perpetrators, whoever they are, regardless of their characteristics or their positions in the state or the Iraqi army. We have concluded, according to the plan followed in the research, that the nature of these crimes is international because the Iraqi text has lost its criminalization and is within the jurisdiction of the International Criminal Court for 1998. It is covered by the Geneva Conventions of 1949. However, the perpetrators may be tried according to Iraqi laws under the principle of judicial complementarity between the national and criminal judiciary.